Psychometric properties of the Persian version of Depression Anxiety Stress Scale-21 Items (DASS-21) in a sample of health professionals: a cross-sectional study - Edris Kakemam; Elahe Navvabi; Ahmed Hassan Albelbeisi; Faeze Saeedikia; Amin Rouhi; Soheila Majidi (BMC, 2022)
Abstract Background Although the Depression Anxiety Stress Scale-21 Items (DASS-21) has been used in different countries and translated into different languages, the Persian version of this scale has not been validated for healthcare professions in Iran. Therefore, the purpose of this study was to examine the psychometric properties of the Persian version of DASS-21 for nurses. Methods This cross-sectional study was conducted among 1135 nurses working in public hospitals, who were selected through convenience sampling. DASS-21, which consists of 21 items and three dimensions (depression, anxiety, and stress), has been translated into Persian, and there is an online version available. A confirmatory factor analysis (CFA) was performed to examine the factor structure of this scale. Cronbach's alpha coefficient was also measured to establish internal consistency. Besides, the intraclass correlation coefficient (ICC) was calculated to assess the test-retest reliability. Results The Cronbach's alpha coefficient was acceptable for anxiety (0.79), stress (0.91), and depression (0.93). An acceptable test-retest reliability (0.740-0.881, P < 0.01) was also reported for DASS-21 and its three dimensions. The results of CFA showed acceptable model fit (χ2/(df) = 1457/(186), P < 0.001), root mean square error of approximation (RMSEA = 0.078), Tucker-Lewis index (TLI = 0.906), comparative fit index (CFI = 0.917), and standardized root mean square residual (SRMR = 0.047). Fifty-seven nurses were included in the test-retest. The ICCs for all dimensions ranged from 0.75 to 0.86, indicating the acceptable test-retest reliability of the scale. Conclusion The Persian version of DASS-21 showed good psychometric characteristics, and it was confirmed as a valid and reliable tool for evaluating depression, anxiety, and stress among Iranian nurses. However, further validation studies of the Persian DSASS-21 are needed among other healthcare professionals, including physicians, midwives, and allied health professionals.